Work Engagement: Determinants and Its Effect On Organizational Citizenship Behavior - Jufrizen; Hazmanan Khair; Anita Permata Sari (Jurnal Manajemen, 2023)
The purpose of this research is to know and analyze the influence of a person's job fit and job crafting on organizational citizenship behavior through work engagement. This study uses a causal type of research using a quantitative approach with a sample of 76 respondents who are employees of the Medan Mayor's Office. To investigate the seven hypotheses proposed in this study, data collection techniques such as interviews and questionnaires were employed, as well as data analysis techniques such as Partial Least Square (SmartPls). The results show that person-job fit has a significant effect on organizational citizenship behavior, job crafting has a significant effect on organizational citizenship behavior, person-job fit has a significant effect on work engagement, job crafting has a significant effect on work engagement, person-job fit has a significant effect on organizational citizenship behavior through work engagement, and job crafting has a significant effect on organizational through work engagement.